Therapeutic hypothermia can be induced and maintained using either commercial water bottles or a "phase changing material" mattress in a newborn piglet model. Issue 5 (20th January 2009) - Iwata, S; Iwata, O; Olson, L; Kapetanakis, A; Kato, T; Evans, S; Araki, Y; Kakuma, T; Matsuishi, T; Setterwall, F; Lagercrantz, H; Robertson, N J
Abstract : Background: Therapeutic hypothermia, a safe and effective treatment for neonatal encephalopathy in an intensive care setting, is not available in low-resource settings. Aims/Methods: To assess two low-tech, low-cost cooling devices for use in low-resource settings: (i) commercially available water bottles filled with tepid water (25°C); (ii) a mattress made of phase changing material (PCM) with a melting point of 32°C (PCM works as a heat buffer at this temperature). Eleven anaesthetised newborn piglets were studied following transient hypoxia–ischaemia. The cooling device was applied 2–26 h after hypoxia–ischaemia with a target rectal temperature (Trectal ) of 33–34°C. Trectal undershoot was adjusted using cotton blankets; the cooling device was renewed when Trectal rose above 35°C. Trectal data during cooling were dichotomised (within or without target) to assess: (a) the total period within the target Trectal range; (b) the stability and fluctuation of Trectal during cooling. Results: Therapeutic hypothermia was achieved with both water bottles (n = 5) and the PCM mattress (n = 6). The mean (SD) time to reach target Trectal was 1.8 (0.5) h with water bottles and 1.9 (0.3) h with PCM. PCM cooling led to a longer period within the target Trectal range (p<0.01) and more stable cooling (p<0.05). Water bottle cooling required device renewal (in four out of five piglets). Conclusion: Simple, low-tech cooling devices can induce and maintain therapeutic hypothermia effectively in a porcine model of neonatal encephalopathy, although frequent fine tuning by adjusting the number of blankets insulating the piglet was required to maintain a stable temperature. PCM may induce more stable cooling compared with water bottles.